2008
DOI: 10.1021/pr800561r
|View full text |Cite
|
Sign up to set email alerts
|

Combining Proteomics and Metabolite Analyses To Unravel Cadmium Stress-Response in Poplar Leaves

Abstract: A proteomic analysis of poplar leaves exposed to cadmium, combined with biochemical analysis of pigments and carbohydrates revealed changes in primary carbon metabolism. Proteomic results suggested that photosynthesis was slightly affected. Together with a growth inhibition, photoassimilates were less needed for developmental processes and could be stored in the form of hexoses or complex sugars, acting also as osmoprotectants. Simultaneously, mitochondrial respiration was upregulated, providing energy needs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
104
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 41 publications
(109 reference statements)
12
104
3
3
Order By: Relevance
“…Thus, it is essential to understand cadmium toxicity and detoxification in the bark of P. 3 canescens to restrict recycling of cadmium to roots, particularly in terms of using P. 3 canescens to remediate cadmium-polluted soils. Although responses of poplars to cadmium stress have been investigated at the proteomic and physiological levels (Schützendübel et al, 2002;Kieffer et al, 2008Kieffer et al, , 2009aKieffer et al, , 2009bDurand et al, 2010;He et al, 2011), the microstructural, transcriptomic, and physiological mechanisms underlying cadmium toxicity and detoxification remain unknown in the bark of poplars.…”
mentioning
confidence: 99%
“…Thus, it is essential to understand cadmium toxicity and detoxification in the bark of P. 3 canescens to restrict recycling of cadmium to roots, particularly in terms of using P. 3 canescens to remediate cadmium-polluted soils. Although responses of poplars to cadmium stress have been investigated at the proteomic and physiological levels (Schützendübel et al, 2002;Kieffer et al, 2008Kieffer et al, , 2009aKieffer et al, , 2009bDurand et al, 2010;He et al, 2011), the microstructural, transcriptomic, and physiological mechanisms underlying cadmium toxicity and detoxification remain unknown in the bark of poplars.…”
mentioning
confidence: 99%
“…In reality, it can be stated that various physiological responses of poplars exposed to heavy metals can be due to genotype, different growth substrates, plant physiological conditions, type of heavy metal and time periods of exposure to heavy metals (Menon et al 2007;Borghi et al 2008). Kieffer et al (2009) demonstrated that a short-term Cd treatment (14 days) had a strong negative effect on the photosynthetic process, but for a long-term Cd treatment (up to 56 days), this effect was lower. In fact, in longterm treatments, some poplars can adapt to heavy metals to minimize the negative impacts on photosynthesis and growth (He et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, proteins with altered synthesis due to changes in gene expression may be used to design molecular markers for the selection of genotypes (Kieffer et al 2009, Regier et al 2009, Visioli et al 2010). However, Scippa et al (2008) have studied the complex mechanism involved in the reaction of root biology to environmental stress.…”
Section: Breeding For Phytoremediationmentioning
confidence: 99%